PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSAN PIDANA TERHADAP PELAKU PENCURIAN YANG MENDERITA KLEPTOMANIA - Septiadi Widagdo, Andreas; Muh Haryanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
This research aims to analyze the judge's considerations regarding criminal acts of theft committed by kleptomania sufferers. This research also aims to examine the application of material criminal law by judges in handing down decisions and sentences against perpetrators of theft who suffer from kleptomania in Decision Number 32/Pid.B/2018/PN Kpg. This research uses a normative method with a statutory approach and a case approach. Primary and secondary legal materials are used as legal sources. The data collection technique was carried out by collecting data from various literature sources relevant to the research. The legal issue in this research is the existence of legal uncertainty in the application of Article 44 of the Criminal Code relating to perpetrators of criminal acts of theft who suffer from kleptomania, as in the case of Decision No32/Pid.B/2018 /PN Kpg above, it was explained that the defendant Maudy Susana Tefnai had a habit of stealing (Kleptomania), for which the defendant Maudy had to undergo criminal probation for 1 year. This is contrary to the Reason for Forgiveness, which states that whoever commits an act that cannot be accounted for because his or her intellectual powers (zijner verstandelijke vermogens) are disabled in growth or impaired due to disease, is not punished. From the trial process in this case, the responsibility of criminals suffering from kleptomania can be analyzed based on monistic and dualistic currents.